2022
DOI: 10.1161/svin.121.000101
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Recanalization of Large‐Vessel Occlusions by Tissue Plasminogen Activator Occurs in 28% of Patients Treated in a Mobile Stroke Unit

Abstract: Background Recanalization of cerebral large‐vessel occlusions (LVOs) by intravenous thrombolysis is infrequent but has been relatively unexplored with ultraearly treatment. We evaluated prehospital treatment with tissue plasminogen activator (tPA) in a mobile stroke unit to explore the recanalization rate in patients with LVOs and its effect on early clinical improvement and long‐term disability. Methods Prospectively collected data were analyzed from H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Achieving early reperfusion in an acute ischemic stroke strongly influences clinical outcomes. [1][2][3][4] In large vessel occlusion (LVO) patients treated with intravenous alteplase, the reported rates of thrombolytic agent-induced reperfusion prior to endovascular therapy ranges from 10 to 30%. [5][6][7][8] Alteplaseinduced reperfusion is associated with several factors, including occlusion site, thrombus permeability, and the time from thrombolytic to subsequent imaging assessment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving early reperfusion in an acute ischemic stroke strongly influences clinical outcomes. [1][2][3][4] In large vessel occlusion (LVO) patients treated with intravenous alteplase, the reported rates of thrombolytic agent-induced reperfusion prior to endovascular therapy ranges from 10 to 30%. [5][6][7][8] Alteplaseinduced reperfusion is associated with several factors, including occlusion site, thrombus permeability, and the time from thrombolytic to subsequent imaging assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving early reperfusion in an acute ischemic stroke strongly influences clinical outcomes 1–4 . In large vessel occlusion (LVO) patients treated with intravenous alteplase, the reported rates of thrombolytic agent‐induced reperfusion prior to endovascular therapy ranges from 10 to 30% 5–8 .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined outcomes in patients with large vessel occlusions presenting directly to the endovascular center emergency department who were randomly assigned to receive rtPA or not, prior to endovascular thrombectomy, with conflicting results 42-44 . While rtPA is relatively ineffective in dissolving a large vessel occlusion, it can do so in 10% to 30% of cases, 45 particularly if administered in the first hour after last time known well and given 30 to 60 minutes to work. A recent meta-analysis of patients presenting to nonendovascular thrombectomy centers with large vessel occlusions showed that outcomes were better if rtPA was given prior to transfer to the endovascular center than if it was skipped 46 .…”
Section: Interaction With Endovascular Thrombectomymentioning
confidence: 99%
“…I ntravenous thrombolysis (IVT) is one of the most effective acute ischemic stroke (AIS) treatments, yet it is delivered only to 2-5% of patients with AIS, due to delayed hospital presentation. 1 Moreover, nearly 30% of patients with AIS get recanalization after the tissue plasminogen activator (tPA) administration, particularly patients with large-vessel occlusion stroke, 2,3 raising the importance of not only the timely IVT administration but also the ability to recognize and triage large-vessel occlusion stroke cases to comprehensive stroke centers (CSCs). 1 Hence, the mobile stroke unit (MSU) was proposed as the "myriad-win" solution accordingly, for its ability to diagnose AIS, establish IVT eligibility, increase the rate of timely IVT administration and even speed administration into the golden hour (the first 60 minutes after symptom onset), [4][5][6] and promptly recognize and transport patients with large-vessel occlusion stroke to CSCs.…”
mentioning
confidence: 99%